Hubungan Kepercayaan Diri Dengan Hasil Belajar Matematika Siswa Kelas X SMAN 1 2x11 Kayu Tanam - Roza, Novia; Jumrawarsi, Jumrawarsi; Rafulta, Elfa (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This research began with the decline in mathematics learning outcomes for class X students at SMAN 1 2X11 Kayutanam. Factors that cause low student mathematics learning outcomes include internal factors, namely student self-confidence. The aim of this research is to determine the relationship between self-confidence and mathematics learning outcomes for class X students at SMAN 1 2x11 Kayutanam. The hypothesis of this research is that there is a relationship between self-confidence and the Mathematics learning outcomes of class X students at SMAN 1 2x11 Kayutanam. This type of research uses quantitative descriptive methods. The population in this study were class X students of SMAN 1 2x11 Kayutanam for the 2022/2023 academic year. The sampling technique in the research was taken using systematic sampling, totalling 43 class X students. The instrument used in this research was a questionnaire given to students. The analytical technique used to test the hypothesis is Pearson product-moment correlation analysis and using the t-test to determine the relationship between self-confidence and Mathematics learning outcomes for class X SMAN 1 2x11 Kayutanam students. The results of the research show that there is a relationship between self-confidence and the Mathematics learning outcomes of class X SMAN 1 2x11 Kayutanam studen. The results of the research show that there is a relationship between self-confidence and the Mathematics learning outcomes of class X SMAN 1 2x11 Kayutanam, whichis indicated by at tstat value of 2,663 and ttable of 1,682 at a 5% error level.Penelitian ini berawal dari menurunnya hasil pembelajaran matematika siswa kelas X SMAN 1 2x11 Kayutanam. Faktor yang menyebabkan rendahnya hasil belajar matematika siswa di antaranya adalah faktor internal yaitu kepercayaan diri siswa. Tujuan penelitian ini adalah untuk mengetahui hubungan kepercayaan diri dengan hasil belajar matematika siswa kelas X SMAN 1 2x11 Kayutanam. Hipotesis penelitian ini terdapat hubungan antara kepercayaan diri dengan hasil belajar Matematika siswa kelas X SMAN 1 2x11 Kayutanam. Jenis penelitian ini menggunakan metode deskriptifÂ kuantitatif. Populasi dalam penelitian ini adalah siswa kelas X SMAN 1 2x11 Kayutanam Tahun Ajaran 2022/2023. Teknik sampel dalam penelitian diambil dengan menggunakan sampling sistematis yang berjumlah 43 siswa kelas X. Instrumen yang digunakan dalam penelitian ini pada berupa angket yang diberikan kepada siswa. Teknik analisis yang digunakan untuk menguji hipotesis adalah analisis korelasi pearson product moment dan menggunakan uji t agar dapat mengetahui hubungan kepercayaan diri dengan hasil belajar Matematika siswa kelas X SMAN 1 2x11 Kayutanam. Hasil penelitian menunjukkaan adanya hubungan kepercayaan diri dengan hasil belajar Matematika siswa kelas X SMAN 1 2X11 Kayutanam yang ditunjukkan dengan nilai thitung sebesar 2,663 dan ttabel sebesar 1,682 pada taraf kesalahan 5%.